Individual differences in the concordance of self‐reports and official records. (October 2014) - Forrest, Walter; Edwards, Benjamin; Vassallo, Suzanne; Farrington, David P.; Ttofi, Maria M.
ABSTRACT Background Although self‐reported and official measures of criminal behaviour are highly correlated, the concordance between self‐reports and official records appears to vary across the population. Few studies, however, have considered the range of individual traits and characteristics that might influence the relative accuracy of self‐reports and official records. Method Using data collected from the Australian Temperament Project, we investigated the concordance between official records and self‐reports together with some of the factors that might influence it. Results Those with criminal records were 3.5 times more likely to report police contact than those with no criminal record. However, there were significant sources of individual‐level variation in their convergence, and notably honest respondents were less likely to report an interaction with police. Those at risk of crime and delinquency were less likely to consent to official records searches. Conclusions Many individual characteristics that predisposed individuals towards a criminal career also affected their willingness to consent to official records searches and the concordance between criminal records and self‐reports. Copyright © 2014 John Wiley & Sons, Ltd.